WADY WRODZONESystemic inflammatory response syndrome in children with hypoplastic left heart syndrome after a modified Norwood operation - Składzień, Tomasz; Wójcik, Elżbieta; Skalski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Systemic inflammatory response syndrome (SIRS) may develop following all extensive cardiosurgical procedures, like in children with hypoplastic left heart syndrome (HLHS), after each stage of surgical treatment of the defect, as a complication of a complex surgical procedure. A prospective analysis was performed in a group of children with hypoplastic left heart syndrome treated with a modified Norwood operation at the Paediatric Cardiosurgery Department of the Polish-American Pediatry Institute in Krakow, in 2007-2009. The study group consisted of 30 patients, including 26 (86.7%) male and 4 (13.4%) female neonates. SIRS was found in 14 (46.6%) patients. In the study group of 30 children, seven (23.3%) died, including five with SIRS and two without SIRS. The study group included 30 children, SIRS was found in 14 (46.6%) patients; seven (23.3%) of 30 children died, including five with SIRS and two without SIRS. Average hospitalization time was 44.4 days (8-138 days), and stay at the intensive care unit was on average 18.5 days (6-82 days). Children in whom generalised inflammatory response deve-loped required more extensive hospitalisation and stay at the Intensive Care Unit. In the group of children with HLHS, patients with SIRS had higher mortality rate compared to the group with HLHS and non-SIRS symptoms. It also showed that the length of time of cardiopulmonary bypass affect the occurrence of SIRS in the postoperative period.